Application of the Design Thinking Concept in the Design of Digital Content for the Smart Village Program in Kertayasa Village - Abung Supama Wijaya; Hudi Santoso; Wahyu Budi Priatna; Ahmad Aulia Arsyad; Leonard Dharmawan (LPPM Universitas PGRI Sumatera Barat, 2025)
The rapid advancement of information technology offers significant opportunities for rural transformation through the Smart Village concept. However, many residents still lack awareness and understanding of the benefits and implementation of Smart Village programs. This study aims to analyze how the Design Thinking theory can be applied in the design of digital content to increase public awareness of Smart Village initiatives in Kertayasa Village. Utilizing a qualitative method, the research employs Focus Group Interviews (FGIs) with 13 active social media users in the village, and in-depth interviews with village officials. The study adopts the Design Thinking framework a user-centered theory consisting of five stages: empathize, define, ideate, prototype, and test. As a result, four digital posters and four short videos were created and distributed via WhatsApp and TikTok, the most commonly used platforms by the community. The findings reveal that the digital content significantly improved residents' understanding and pride in the Smart Village programs, especially in the areas of waste management (TPS 3R), SIMAK, and digital library. The novelty of this study lies in the contextual application of Design Thinking for content development in a rural digital literacy context, a topic that remains underexplored in existing literature. In conclusion, Design Thinking is proven to be an effective and adaptive method for designing impactful, user-centered digital communication strategies in rural development initiatives